Rapid identification of cyclic Tetrapyrrolic Photosensitisers for Photodynamic therapy using on-line hyphenated LC-PDA-MS coupled with photo-cytotoxicity assay - Tan, P.J.; Appleton, D.R.; Mustafa, Mohd Rais; Lee, H.B. (2011)
Introduction â Photodynamic therapy is a treatment modality that involves siteâdirected generation of cytotoxic reactive oxygen species by lightâactivated photosensitisers. Objective â In order to rapidly identify new photosensitisers from natural extracts, we developed a liquid chromatographyâphotodiode arrayâmass spectrometry (LCâPDAâMS) method to rapidly identify plant extracts that contain photosensitisers, particularly those possessing a cyclic tetrapyrrole structure. Method â Six previously isolated compounds (1â6) were identified in bioactive fractions derived from 15 plant extracts on the basis of their chromatographic retention times, UVâvisible profiles, accurate mass and fragmentation patterns. Results â Samples containing uncommon photosensitisers were rapidly identified using this method, and subsequent scaleâup isolation efforts led to two new compounds (7 and 8) which were confirmed to be active photosensitisers in a photoâcytotoxicity assay. Conclusion â This method serves as a useful tool in prioritising samples that may contain new photosensitisers out of a larger group of photoâcytotoxic natural products extracts. Copyright Â© 2011 John Wiley & Sons, Ltd.